Epidemiology of Anguina agrostis on Highland Colonial Bentgrass - Pinkerton, J N (Journal of nematology, 1994)
The epidemiology of Anguina agrostis was investigated in field plots of Colonial bentgrass (cv. Highland), Agrostis tenuis, near Corvallis, Oregon. Each October from 1990-92, nylon mesh pouches, each containing 10 galls, were buried in the field or placed on the soil surface in microplots. Pouches were collected monthly or bimonthly between December and June and nematodes per gall counted. Nematode egression from galls began in late March and was completed by mid-May, corresponding to the period of floral initiation in bentgrass. In 1991 and 1992, 0.09-m(2) plots were inoculated with 0, 1, 5, 15, 50, 120, or 200 galls/plot. The disease severity (number of galls) and disease incidence (% seed heads with galls) increased linearly at inoculum densities below 50 galls/ plot. At higher inoculum densities, disease increase approached an asymptote. In 1991, plots were established to determine the characteristics of disease spread. Disease foci were established by placing 0, 5, 50, or 500 galls along 30-cm sections of row in the fall. In July 1992, seed heads were harvested at 30 and 60 cm from each focus within and across plant rows. Most infestations were found within 30 cm of foci at all inoculum levels. At high inoculum densities, the distribution of galls was aggregated with the majority of galls located on less than 10% of the seed heads. These disease spread and incidence data suggest populations of A. agrostis increase slowly in bentgrass in Oregon